Congenital retroperitoneal vascular anomalies: Impact on pelvic surgery - Strauss, Alexander; Kuemper, Carolin; Mundhenke, Christoph; Schaefer, Fritz; Jonat, Walter; Hilpert, Felix (Archives of Gynecology and Obstetrics, 2011)
Purpose Congenital anomalies of the inferior vena cava (IVC) are not commonly recognized since they generally do not cause symptoms. Methods Preoperative cross-sectional imaging can identify anomalies of vascular structures that are highly relevant to the pelvic surgeon. The clinical impact of congenital vascular variations of IVC, especially on paraaortic lymphadenectomy, is investigated Results In case the surgeon is unaware of these anomalies, impending differential diagnostic confusion (paraaortic adenopathy), intraoperative blood loss and the need for transfusion may occur. The development of IVC is a complex process concerning the formation of several anastomoses between three paired embryonic veins (posterior cardinal, subcardinal, supracardinal veins). In double IVC, the left IVC typically ends at the level of the left renal vein, in an anastomosis which crosses anterior to the aorta to join the normal right IVC. Conclusion Anomalies of IVC are present in 0.4-3.5% of women. As different aberrations of IVC have important clinical implications, awareness of retroperitoneal abnormal vessels is crucial to avoid diagnostic pitfalls and intraoperative complications. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Computerized tomography; Double inferior vena cava (IVC); Gynaecological cancer; Paraaortic lymphadenectomy; Pelvic surgery